Analisis Beban Kerja dalam Upaya Peningkatan Kinerja Karyawan Non-Medis Divisi Casemix Rumah Sakit XYZ Karawang - Sukma Ali Wibowo; R.M. Juddy Prabowo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze workload in an effort to improve the performance of non-medical employees in the Casemix Division of XYZ Hospital, Karawang. The research method used a qualitative approach, with data collection techniques through observation, interviews, documentation, and literature review. Informants in this study consisted of the verification coordinator, the BPJS claims coordinator, two verification teams, and two BPJS claims teams. The results indicate that the workload of Casemix Division employees is relatively high, as indicated by an imbalance between the number of tasks and the number of employees, multiple assignments, data input errors, suboptimal claim administration, and system constraints on the BPJS claims website. Furthermore, the use of working time is inefficient, resulting in employees frequently working overtime to complete their work. Work targets are also often not achieved due to limited human resources and the accumulation of work from the previous month. These conditions impact employee performance, as evidenced by the lack of work performance, limited skills of some employees, a lack of training programs, and inaccurate completion of work. In conclusion, the high workload impacts the low performance of non-medical employees in the Casemix Division. Therefore, additional human resources, competency development through training, and work system improvements are needed to enhance employee effectiveness and performance. Keywords: Workload, Employee Performance, Human Resources, Casemix, Hospital